Multiagent based selection of tutor-subject-student paradigm in an intelligent tutoring system - Mishra K.; Mishra R.B. (My University, 2025)
Intelligent tutoring systems (ITS) aim atdevelopment of two main interconnected modules: pedagogical module and student module. The pedagogical module concerns with the design of a teaching strategy which combines the interest of the student, tutor's capability and characteristics of subject. Very few effective models have been developed which combine the cognitive, psychological and behavioral components of tutor, student and the characteristics of a subject in ITS. We have developed a tutor-subject-student (TSS) paradigm for the selection of a tutor for a particular subject. A selection index of a tutor is calculated based upon his performance profile, preference, desire, intention, capability and trust. An aptitude of a student is determined based upon his answering to the seven types of subject topic categories such as Analytical, Reasoning, Descriptive, Analytical Reasoning, Analytical Descriptive, ReasoningDescriptive and Analytical Reasoning Descriptive. The selection of a tutor is performed for a particular type of topic in the subject on the basis of a student's aptitude. Copyright © 2010, IGI Global.